2015
DOI: 10.1111/1346-8138.13040
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profiles and treatment outcomes of systemic corticosteroids for toxic epidermal necrolysis: A retrospective study

Abstract: Toxic epidermal necrolysis (TEN) is an uncommon severe cutaneous adverse reaction. Although controversies remain in the pathophysiology and management of this condition, improvements in survival and morbidity have been observed over the past decade. The aim of the present study was to demonstrate the clinical profiles of TEN in Thai patients and the treatment outcome with dexamethasone pulse therapy assessed by using the Severity of Illness Score for Toxic Epidermal Necrolysis (SCORTEN). Medical records of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
(53 reference statements)
0
4
1
1
Order By: Relevance
“…Because corticosteroids could theoretically increase the risk of sepsis, its use in patients with extensive skin detachment is not widespread. Coinciding with a multicentre study of the RegiSCAR group, 53 the results of this study do not support an increase in mortality with the use of systemic corticosteroids 25,32,38,40,50,52,54‐58 …”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Because corticosteroids could theoretically increase the risk of sepsis, its use in patients with extensive skin detachment is not widespread. Coinciding with a multicentre study of the RegiSCAR group, 53 the results of this study do not support an increase in mortality with the use of systemic corticosteroids 25,32,38,40,50,52,54‐58 …”
Section: Discussioncontrasting
confidence: 54%
“…The use of systemic corticosteroids in patients with SSJ/NET has not been evaluated in clinical trials, except in a study in comparison with etanercept, in which no significant differences were found in overall survival 50 . There is an ongoing debate about the use of CE in this condition; however, given dose disparities, different indications 51 and the ages of the studies, it is difficult to reach any conclusions about its effectiveness as a monotherapy 32,52 . Because corticosteroids could theoretically increase the risk of sepsis, its use in patients with extensive skin detachment is not widespread.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a systematic study of glucocorticoids used in the treatment of SJS/ TEN in Thailand showed that early systemic glucocorticoid short-term pulse therapy was beneficial in reducing mortality. 16 All patients in this study were systematically treated with glucocorticoids, and the actual mortality rate was 1.8%, which was significantly lower than the overall expected mortality rate of 15.0%. The SMR results also showed that the actual number of deaths was lower than the expected number of deaths.…”
mentioning
confidence: 66%
“…En los pacientes con SSJ/NET, en estudios en donde fueron administrados en fases avanzadas de la enfermedad (después del quinto día desde el inicio de los síntomas) no fue posible evaluar si existe o no beneficio (13) ; sin embargo, al administrarse en fases tempranas de la enfermedad (menos de 72 horas) pulsos de dexametasona en dosis de 1,5 mg/kg durante 3 días, se demostró una reducción de las secuelas oculares (14) y una disminución del tiempo de recuperación de las lesiones, sin efecto sobre la mortalidad (15,16) . Otro esquema que podría presentar resultados positivos es propuesto a partir del reporte de caso presentado por Middendorf y colaboradores, donde se utilizan corticoides sistémicos con ácido ascórbico y tiamina, lo que se ha denominado terapia HAT, por sus siglas en inglés (hydrocortisone, ascorbic acid and thiamine), con el que se obtuvo control y resolución de la enfermedad (17) .…”
Section: Corticoides Sistémicosunclassified